Short-Term Fever-Range Hyperthermia Accelerates NETosis and Reduces Pro-inflammatory Cytokine Secretion by Human Neutrophils - Keitelman, Irene A.; Sabbione, Florencia; Shiromizu, Carolina M.; Giai, Constanza; Fuentes, Federico; Rosso, David; Ledo, Camila; Miglio Rodriguez, Maximiliano; Guzman, Mauricio; Geffner, Jorge R.; Galletti, Jeremías; Jancic, Carolina; et al. (Frontiers in Immunology, 2019)
Fever is a hallmark of infections and inflammatory diseases, represented by an increase of 1°C to 4°C in core body temperature. Fever hyperthermia has shown to increase neutrophil recruitment to local sites of infection. Here we here evaluated the impact of a short period (1 h) of fever-range hyperthermia (STFRH) on pro-inflammatory and bactericidal human neutrophil functions. STFRH did not affect neutrophil spontaneous apoptosis but reverted the LPS-induced anti-apoptotic effect compared to normothermic conditions. Furthermore, STFRH accelerated PMA-induced NETosis evaluated either by the nuclear DNA decondensation at two hours post-stimulation, as well as by the increase in extracellular DNA that colocalized with MPO at 4 hours post-stimulation. Increased NETosis upon STFRH was associated with an increase in reactive oxygen species production but not in autophagy levels. STFRH also increased NETosis in response to P. aeruginosa challenge but moderately reduced its phagocytosis. However, these STFRH-induced effects did not influence the ability of neutrophils to kill bacteria after 4 h of co-culture. STFRH also significantly reduced neutrophil capacity to release the pro-inflammatory cytokines CXCL8/IL-8 and IL-1β in response to LPS and P. aeruginosa challenge. Altogether, these results indicate that a short and mild hyperthermal period is enough to modulate neutrophil responses to bacterial encounter. They also suggest that fever spikes during bacterial infections might lead neutrophils to trigger an emergency response promoting NETs formation to ensnare bacteria in order to wall off the infection but to reduce their release of proinflammatory cytokines in order to limit the inflammatory response.